Assessment of parent's oral health literacy and its association with caries experience of their preschool children attending Hospital Universiti Sains Malaysia - Adil, Abdul Habeeb (2020)
Oral health literacy (OHL) is an important aspect of oral health and general well-being of an individual. The OHL includes reading, writing, speaking, listening, appropriate decision making and numeracy skills. The OHL of parents plays an important role in the prevention of dental caries among their children. This study aimed to assess the OHL of parents and its association with the caries experience of their preschool children. This was a descriptive cross-sectional study involving a systematic random sampling method, using a sample of 230 parent/preschool child pair attending the pedodontics clinic, Hospital Universiti Sains Malaysia (Hospital USM), who participated and met the inclusion criteria. A structured, self-administered OHLI-M questionnaire including sociodemographic factors was used in this study. A child’s oral examination was performed to check the dmft (decayed, missing, filled teeth) status. Statistical analysis was done using descriptive, multivariate regression analysis and one-way Anova with post-hoc analysis. Among 230 parents, 24 were males and 206 were females with mean age (31.43 ± 5.82) years old, among children, 92 were boys and 138 were girls with mean age (4.82 ± 1.04) years old participated in this study. The participants are divided into 3 groups depending upon ethnicity. Most of the parents were educated with a basic degree, and more parents were employed. The mean OHL score of the parents was (58±27.39). The inadequate OHL level (43.9%) of parents was more followed by adequate OHL level (31.3%) and then marginal OHL level (24.8%). The caries prevalence among the preschool children was 68.7% and 31.3% were caries free. The mean dmft score was (4.27±4.36), where a higher mean dmft was noted amongst children with 6 years of age followed by 5 years, 4 years and then 3 years old. The age (p<0.001) and gender (p=0.01) of preschool children was significant in relation to their dmft score. The multiple regression analysis showed that after adjustment for sociodemographic factors, parents’ gender (OR = 5.921, 95% CI: 1.355–25.879), parents’ employment status (OR = 0.273, 95% CI: 0.079–0.941), parents’ OHL score (OR = 16.122, 95% CI: 5.846–44.462), and child age (0.018, 95% CI: 0.014–0.816) were significantly associated with caries experience in children. Significant difference was found between dmft score and all the levels of OHL with p-value < 0.05. Further, significant difference was found between education of parents and dmft score of preschool children with p-value < 0.05. We conclude that there is a significant association between the OHL of parents with the caries experience of their preschool children.